Enzymatic hydrolyzation of mogrosides in Luo Han Guo extract by NKA-adsorbed snailase improves its sensory profile. (1st October 2022) - Su, Yongxin; Li, Zhenlin; Zhao, Yinghui; Chen, Yijun; Luo, Chen; Wu, Xuri
Graphic abstract: Highlights: Snailase can improve the taste of LHG extract that suffers from an aftertaste. NKA-adsorbed snailase was superior to modify LHG extract. A continuous approach was established to produce improved LHG extract. The safety of improved LHG extract was determined by in vitro cytotoxicity testing. Abstract: Extracts of Siraitia grosvenorii (Swingle), in Chinese known as Luo Han Guo (LHG), is authorized for use as a natural sweetener. LHG is rich in mogroside V that contains five glucoses, but also contains mogroside IIIE and analogues with fewer than three glucose units that cause an unpleasant aftertaste, limiting the use of the extract. Snailase was applied here to convert mogroside V in LHG extract in favor of siamenoside I formation, the sweetest mogroside with a taste similar to sucrose. For application, snailase was immobilized by adsorption to NKA (a macroporous resin), resulting in 10.9 U per g of adsorbed protein. Reuse of the NKA-adsorbed snailase was demonstrated for four cycles, and a continuous production of improved LHG extract at a 0.5 L scale had a productivity of 68.4 g/(L⋅day). The resulting product containing over 50% siamenoside I displayed an improved taste profile with satisfying safety toward HEK293T cells.